Influence of radiation exposure on the properties of dielectric layers based on anodic aluminum oxide - S. A. Biran; D. A. Korotkevich; A. V. Korotkevich; K. V. Garifov; A. D. Dashkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
Devices that are used in the aerospace industry must operate in extreme conditions, so it is important to understand how the properties of materials change under the influence of radiation and low temperatures. Anodic aluminum oxide, due to its mechanical and dielectric properties, is widely used in electronic devices with a high degree of integration. Radiation exposure can lead to degradation of the electrophysical parameters of dielectric films and can also change their chemical composition. The methods for studying the effect of radiation exposure on the dielectric properties of films are shown in this article. The research has been carried out and the results of the influence of α-particles on the dielectric properties of a porous film of anodic aluminum oxide during the influence of low temperature are presented.